Quantifying magnetic exchange in doubly-bridged Cu-X(2)-Cu (X = F, Cl, Br) chains enabled by solid state synthesis of CuF(2)(pyrazine). - Lapidus, S; Manson, J; Liu, J; Smith, M; Goddard, P; Bendix, J; Topping, C; Singleton, J; Dunmars, C; Mitchell, J; Schlueter, J (2013)
Solid state techniques involving pressure and temperature have been used to synthesize the fluoride member of the CuX(2)(pyrazine) (X = F, Cl, Br) family of coordination polymers that cannot be crystallized by solution methods. CuF(2)(pyrazine) exhibits unique trans doubly-bridged Cu-F(2)-Cu chains that provide an opportunity to quantify magnetic superexchange in an isostructural Cu-X(2)-Cu series.